The Effect of Location On The Sales Volume of Bumi Kenanga II Housing PT. Sangkuriang Medal Pratama Sumedang - Puspasari, Rd. Dewi; Damayanti, Wulan Ariani; Mulyana, Atep (Journal of Bussines Management Basic, 2025)
Location is very important in increasing sales volume and increasing the success of the company. This study aims to find out how much the location affects the sales volume of Bumi Kenanga Asri II Housing in PT. Sangkuriang Medal Pratama. This study uses a quantitative approach. The research methods used are descriptive and verifiable. The sampling technique used was non-probability sampling with a sample population of 49 people because it used saturated samples. The analysis methods used were normality tests, simple linear analysis, correlation analysis, determination coefficients, and hypotheses using the SPSS 25 program. The results showed that location had a positive and significant effect on purchase decisions by 61.0% while the remaining 39.0% were influenced by other variables that were not studied.